The role of counselling, monitoring of serum carbamazepine concentration, and of compliance in epilepsy control - Bridgens, Rosalie Anne (University of Limpopo (Medunsa Campus), 2014)
i THE ROLE OF COUNSELLING, MONITORING OF SERUM CARBAMAZEPINE CONCENTRATION, AND OF COMPLIANCE IN EPILEPSY CONTROL Non-compliance with the patient’s prescribed medication regimen has been identified in several publications as a major factor responsible for insufficient seizure control. Non-compliance is also held by some workers in this field to be closely interlinked with inadequate serum anti-epileptic drug concentration. The early identification of non-compliance may therefore play an important role in epilepsy therapy. A study was undertaken at Kalafong Hospital to explore the efficacy of monitoring serum carbamazepine concentration in order to detect compliance or otherwise. Intrinsic in such study was exploration of the role played by counselling in the promotion of compliance. Samples of blood were drawn from 78 outpatient volunteers at intervals as close to 28 days as possible, and the serum carbamazepine concentration of these samples was then determined by means of the TDx FLx System (ABBOTT). Items such as conscientious attendance at the Kalafong epilepsy clinics (“visits”), serum carbamazepine concentration, patient’s age, gender and weight, concomitant drug interactions, occurrence of epileptic seizures and dosage of Tegretol®CR were examined to ascertain whether they could be correlated with compliance and used as indicators thereof. It was, however, constantly borne in mind that these are not the only elements of compliance; other factors such as difficult fundamental behavioural changes, such as avoiding stress, may also play a part. Conscientious attendance at Kalafong epilepsy clinics (“visits”) was found to be a usable (albeit not strong) indicator of compliance. Serum carbamazepine concentration was used as another, with, however, reservations arising from the relationship between the patient’s actual compliance on the one hand, and whether v the daily dosage was sub-therapeutic or excessive on the other. The statistical agreement between visits and these concentration values was, however, very poor (8.2%). Using visits as an indicator, 66.7% of the participants were assessed as compliant. Using ‘compliant concentration’, only 25.6% were assessed as compliant. The data acquired during the study was, unfortunately, too variable to warrant anything more than descriptive statistical treatment. To a large extent this was because the participants were out-patients, not in-patients over whom strict therapeutic control could be exercised. Age, gender and patient’s weight were not significantly linked to compliance. The correlation between expected and measured serum carbamazepine concentrations was not statistically significant (p = 0.062). The Kalafong data in respect of seizures indicate that the relationship between seizures and compliance is not a simple one and that the occurrence or otherwise of break-through seizures should not be used as an indicator of compliance, as has indeed been done by other research workers. Drug interaction was as expected in 20 of the 26 patients concerned, this agreement being statistically significant (p = 0.0074). Improved compliance was the outcome expected from counselling but it was not possible to quantify the enhancement of compliance achieved, if any. Conventional verbal counselling, particularly when not done in the patient’s mother tongue and supported by interventions such as visual counselling material, may not be adequate.
Thesis (MSc(Med)(Pharmacy))-- University of Limpopo, 2012.
Keywords: Serum.; Serum bactericida test